Evaluation and additional recommendations for preparing a whole blood control material Avaliação e recomendações adicionais para a preparação de material sangüíneo integral para controles - Nilda E. Fink; Alejandra Fernández Alberti; Isabel Crispini; Norberto V. Cabutti; Daniel Mazziotta (Universidade de São Paulo, 1998)
OBJECTIVE: The assessment of an easy to prepare and low cost control material for Hematology, available for manual and automated methods. MATERIAL AND METHOD: Aliquots of stabilized whole blood were prepared by partial fixation with aldehydes; the stability at different temperatures (4. 20 and 37 °C) during periods of up to 8-9 weeks and aliquot variability with both methods were controlled. RESULTS: Aliquot variability with automated methods at day 1, expressed as CV% (coefficient of variation) was: white blood cells (WBC) 2.7, red blood cells (RBC) 0.7, hemoglobin (Hb) 0.6, hematocrit (Hct) 0.7, mean cell volume (MCV) 0.3, mean cell hemoglobin (MCH) 0.6, mean cell hemoglobin concentration (MCHC) 0.7, and platelets (PLT) 4.6. The CV (coefficient of variation) percentages obtained with manual methods in one of the batches were: WBC 23, Hct 2.8, Hb 4.5, MCHC 5.9, PLT 41. Samples stored at 4ºC and 20ºC showed good stability, only a very low initial hemolysis being observed, whereas those stored at 37ºC deteriobed a rapidly (metahemoglobin formation, aggregation of WBC and platelets, as well as alteration of erythrocyte indexes). CONCLUSIONS: It was confirmed that, as long as there is no exposure to high temperatures during distribution, this material is stable, allowing assessment, both esternal and internal, for control purposes, with acceptable reproductivity, both for manual and auttomatic methods. OBJETIVO: Avaliar material de controle para hematologia, de fácil preparação e baixo custo, que poderá ser usado por métodos manuais e automatizados. MATERIAL E MÉTODO: Alíquotas de sangue estabilizado foram preparadas por fixação parcial com aldeídos. Foram estudadas a estabilidade a diferentes temperaturas (4, 20, 37ºC) durante períodos de até 8-9 semanas e a variabilidade das alíquotas para ambos os métodos. RESULTADOS: A variabilidade entre alíquotas, expressada em CV% (coeficiente de variação) com métodos automatizados no primero dia, foi: glóbulos blancos (WBC) 2,7, glóbulos vermelhos (RBC) 0,7, hemoglobina (Hb) 0,6, hematócrito (Hct) 0,7, volume corpuscular médio (MCV) 0,3, Hb corpuscular médio (MCH) 0,3, concentração de Hb corpuscular médio (MCHC) 0,7 e plaquetas (Plt) 4,6. O CV% obtido com métodos manuais para um dos grupos foi: WBC 23, Hct 2,8, Hb 4,5, MCHC 5,9, Plt 41. As amostras conservadas a 4 e 20ºC foram estáveis, observando-se leve hemólise inicial, enquanto que as amostras conservadas a 37ºC mostraram uma rápida decomposição (formação de metaemoglobina, agregação de glóbulos brancos e plaquetas e alteração de índices). CONCLUSÕES: Confirmou-se que, se não houver exposição a altas temperaturas durante a distribuição, este material é estável, permitindo avaliação, tanto externa como interna para controle e com reprodutividade aceitável, tanto para métodos manuais como automáticos.